A Corpus-Based Critical Discourse Analysis of Gender Representation in ELT Textbooks - Adela Rifa Anbiya; Fadillah Meigiansyah Rizqie; Luthfi Luqmansyah; Nazmara Azka Hidayat; Hapid Ali (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2026)
This study examines the representation of gender in My Next Words Grade 4, a government-mandated compulsory English textbook for elementary students in Indonesia. While prior research has explored gender bias in EFL materials, quantitative critical discourse studies on textbooks introduced under the new Kurikulum Merdeka at the primary level remain scarce. This research employs corpus-assisted critical discourse analysis (CDA) to identify and quantify gender-related references, including pronouns, character names, and visual cues denoting social and domestic roles. Data were processed using AntConc software to examine the frequency of male and female references and their collocational patterns. The findings reveal unequal visibility and role distribution between genders among the textbook's characters, with stereotypical representations persisting despite government efforts to promote gender parity in educational media. Female characters are predominantly associated with domestic activities, while male characters are more frequently depicted in active, public-sphere roles. These results highlight the ideology embedded in official learning materials and underscore the need for curriculum developers to design more balanced, nondiscriminatory gender representations, essential for fostering equitable gender perceptions among young learners. This study contributes empirical insight into ongoing efforts to align Indonesia's educational materials with national gender equality policies.